The Information Revolution and its Impact on War - Mehdi Nazemi Ardakani; Majid Nejatpour; Mostafa Mohammadi (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2016)
The revolution in information and communication technologies plays a prominent role in organizing military operations in the third millennium. The questions here are about the ways that this revolution affects the soft war? Which wars have been affected by revelation of information and communication? And how can information and communication technologies be used in war? The hypothesis is that Modern information and communication technology have led to the formation of new wars such as the space Cyber warfare, and electronic warfare. Information and communication technology revolution, has changed Combat power and military tactics and has played a key role in the victory of wars. With the advent of electronic networks, a fundamental change in power relations appeared, and new players who are flexible and do not follow rule of law posing potential threat to the world order